The Fifth Semester Students' Competence in Mastering English Proverb at English Department of UMMU - Jusmin HJ Wahid; Anita B. Muhammad (English Education Department, Faculty of Education Muhammadiyah University of North Maluku, 2021)
Proverbs usually consist of groups of words or sentences that state the meaning, condition of a person, or things that reveal about a person, actions, behavior, or things.This research aims to determine the extent of students' competence in mastering English proverbS.Then, this research used descriptive qualitative research. The subjects of this study were fifth-semester students at the English Education Study Program at the Muhammadiyah University of North Maluku which consisted of 13 students. In the data collection, the researchers used multiple-choice that was consisting of 20 items of English. The results of this study indicate that the fifth-semester students of the English Education Study Program at the Muhammadiyah University of North Maluku fall into the low category in mastering English proverbs, based on the score obtained by the students, it can be seen from the student test results, namely 21.92%. Therefore, English proverbs should be implemented in English teaching regularly.